STUDY OF FRESHWATER TURTLES IN SELECTED DISTRICTS OF SINDH- PAKISTAN: THREATS, ILLEGAL TRADE AND CONSERVATION - M. Z. Khan; R. Kanwal; S. A. Ghalib (Journal of Animal and Plant Sciences, 2018)
Population estimation of freshwater turtles was conducted in selected localities from seven selected districts of Sindh. Two years surveys were carried out from 2015 to 2016. Eight species of freshwater turtles were recorded from Sindh. In 2015, population of Lissemys punctata (1 6.93%) was found as abundant in most of the districts of Sindh. Pangshura tecta ( 13.05%) and Geoclemys hamiltonii (13.49%) were recorded as common while population of Nilssonia hurum (11.56%) was estimated as less common. Chitra indica (9 .23%) was recorded as rare. In 2016, slight decline in most of the turtle`s populations were observed as Lissemys punctata (15.08%), Pangshura tecta (12.74%), Geoclemys hamiltonii ( 12.02%), Nilssonia hurum (12.6%). Highest ratio of Shannon diversity index ( 2.07) was recorded from Sukkur District while Evenness index was also high in Sukkur district (0.406). Hunting and Illegal trading were recorded as major threats for their survival. Other factors include their usage in pharmaceutical, food industries and as pets. Several measures have been taken for their conservation by IUCN, Sindh Wildlife Department, Zoological Survey Department, and Department of Zoology (Wildlife Section), University of Karachi. of deterioration of natural habitats, environmental
Keywords: Freshwater turtles; Sindh; Population distribution.